“We Will Not Change Our Attitude Towards You, Until You Change Your Attitude Towards Us”. How Washington Considered the Reaction of Western European Communist Parties to The Events in Afghanistan, 1978–1985 - V. T. Yungblud; M. V. Bakshaev (Vestnik MGIMO-Universiteta)
The invasion of a limited contingent of Soviet troops into Afghanistan at the end of 1979 caused a mixed reaction among the Communist parties in Europe. Some of them subject the actions of the USSR leadership to sharp criticism. The article reveals to what extent the US administration was aware of the critical attacks against the USSR and the CPSU by the most powerful Western European Communist parties to determine how the factor of Eurocommunism influenced the Afghan vector of the US policy in 1979-1982 and how the American course turned out for the Communist parties themselves. The study is based on published documents (including electronic collections) of the Administration of the President of the United States J. Carter, the State Department, and the Central Intelligence Agency of the United States, as well as unpublished documents of the Central Committee of the CPSU from the funds of the Russian State Archive of Modern History, press materials and memoirs. It is concluded that 1) the invasion of Soviet military units into Afghanistan provoked a fierce battle of superpowers on the periphery of the Cold War, and in fact, became its peak; 2) one of the results of the Soviet operation was a deeper split in the world communist movement with its subsequent decline; 3) the United States sought to take advantage of the escalated disagreements between the Communist Party of the Soviet Union and the largest communist parties in Western Europe (especially Italian, to a lesser extent Spanish and French) and encouraged the actions of the European Communists aimed at distancing themselves from the CPSU and severing relations with the USSR. At the same time, Washington avoided public statements and actions that could look like a manifestation of solidarity with the Communist parties of Western Europe (primarily with the ICP), including the relation to the USSR policy in Afghanistan, giving priority to the policy to exclude completely the possibility for communists to participate in the governments of NATO states. Such a policy, against the background of the ongoing war in Afghanistan and the decline in the USSR's international prestige, contributed to the isolation of the European communist parties in their countries and the weakening of their electoral opportunities.